Isolation, identification and enzymatic characteristics of a high-yield cellulase fungi - LI Mei, LI Xue, FENG Yulian, JIANG Xingtong, TANG Qiyong, ZHANG Zhidong (Zhongguo niangzao, 2025)
In this study, using Congo red staining method and enzyme activity assay, the high-yield cellulase fungi from soil samples in Turpan area was screened. The screened strain was identified by morphological observation and molecular biology techniques, and the enzymatic characteristics of cellulase produced by the strain were studied. The results showed that a high-yield cellulase fungi 12-3-6 was obtained, and the activity of filter paper enzyme (FPA) and carboxymethyl cellulase (CMCase) in the fermentation broth of the fungi were 7.30 U/ml and 39.56 U/ml, respectively. Strain 12-3-6 was identified as Aspergillus egyptiacus. The results of enzymatic characteristic analysis showed that the optimal reaction conditions of FPA and CMCase produced by strain 12-3-6 fermentation was both reaction temperature 50 ℃ and reaction pH value 5.0. The relative enzyme activity of FPA and CMCase produced by strain 12-3-6 fermentation was still higher after 1 h at 30-60 ℃ or pH 5.0-6.0, and Cu2+ could significantly improve the enzyme activity. Sodium dodecyl sulfate (SDS) had a certain inhibitory effect on enzyme activity. The results indicated that the cellulase produced by strain 12-3-6 had high activity and stable enzymatic properties, and had a good application prospect.